Independent association of serum uric acid levels with arterial stiffness in the absence of established cardiovascular disorders. Issue 3 (13th October 2020) - Kang, Hyeon Hui; Won, Ki‐Bum; Heo, Ran; Han, Donghee; Chang, Hyuk‐Jae
Abstract: Background: The impact of serum uric acid (SUA) on atherosclerosis has been suspected to be epiphenomenal owing to its close relationship with metabolic abnormalities. The aim of the present study was to evaluate the association between SUA levels and arterial stiffness in the absence of established cardiovascular (CV) disorders. Methods: The relationship between SUA levels and brachial‐ankle pulse wave velocity (baPWV) was examined in 353 asymptomatic adults (57 ± 8 years, 11.9% men) without established CV disorders defined as systolic blood pressure (BP) ≥140 mmHg or diastolic BP ≥ 90 mmHg; total cholesterol ≥240 mg/dL; low‐density lipoprotein cholesterol ≥160 mg/dL; high‐density lipoprotein cholesterol <40 mg/dL; fasting glucose ≥126 mg/dL; body mass index ≥25.0 kg/m 2 ; current smoking; and history of medication for hypertension, diabetes, and dyslipidemia. Subjects were stratified into four groups based on the quartiles of their SUA levels. Results: Mean baPWV was significantly different in all groups: group I, 1320 ± 195 cm/s; group II, 1336 ± 195 cm/s; group III, 1404 ± 199 cm/s; and group IV, 1483 ± 248 cm/s ( P  < .001). SUA levels were significantly correlated with baPWV ( r  = .364) ( P  < .001). Multivariate linear regression analysis showed that SUA ( β : 32.93; 95% confidence interval [CI]: 18.99‐54.87), together with age ( β : 11.44; 95% CI: 9.36‐13.53) and systolic BP ( β : 8.98; 95% CI: 6.80‐11.16), was significantly associated with baPWV ( P  < .001). Conclusions: High SUA levels have an independent association with increased arterial stiffness even in subjects without established CV disorders.